Comparative zoobenthos investigations in the Histria and Nuntasi lakes during the period 1971 – 1978 - Nagy, Carol G. (Cercetări Marine - Recherches Marines, 2026)
Zoobenthic investigations were carried out in 1971 - 76 in the oligohaline lakes Histria and Nuntasi, at Romanian Black Sea coast. A brief description is given of the different indicator systems used in evaluating trophic status. A method is performed for calculating abundancy index for Chironomidae populations. Based on the correlation between the quotients obtained for the phytoplanktonic indicators and the results furnished by the Chironomids, it was showed that Histria remained mesotrophic while Nuntasi became eutrophic during the last decade.